2018
DOI: 10.1055/a-0723-4421
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Inflammatory Cytokine Responses to Endurance Exercise in Female Rowers

Abstract: This investigation examined the effects of acute rowing exercise on a panel of 12 different inflammatory cytokines. Fifteen female rowers (18.3±1.6 yrs; 172.0±5.0 cm; 67.5±8.8 kg; maximal oxygen consumption [VO2max]: 47.2±7.9 ml.min.−1kg−1) completed a 1-h endurance exercise (distance: 12.1±1.1 km; energy expenditure [EE]: 639±69 kcal; heart rate: 151±7 beats.min−1; intensity: 79.6±3.5% of the second ventilatory turn point). Venous blood samples were analysed for interleukin (IL)-2, IL-4, IL-6, IL-8, IL-10, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Blood samples collected pre- and post-training In both genders, after test: ↔IL-1ra, ↑IL-6 Eliakim et al 2013 [ 29 ] volleyball 13 female, national team level players, age 16.0 ± 1.4 years GH, IGF-I, IGFB3, C, IL-6, IL-1ra Samples obtained pre-, post-, 1 h post a volley training at preseason and after 7 weeks of preparation In both conditions, athletes had: ↑IL-6, ↔IL-1ra Jurimae at al. 2018 [ 56 ], rowing 15 female rowers, age 18.3 ± 1.6 years IL-2, IL-4, IL-6, IL-8, IL-10, TNF-α, IL-1α, IL-1β, VEGF, MCP-1 Blood samples pre- and 1 h post-endurance exercise ↑IL-6, IL-8, VEGF, MCP-1 Meckel et al 2009 [ 37 ], handball 12 junior handball players, age range 17–20 years GH, IGF, IL-6, IL-1b, IL-1ra, IL-10 Sprint run on a treadmill, at an intensity of 80%. Samples collected at pre-, after each 250-m run, and 60 min post-last 250 m After exercise athletes displayed: ↑IL-6, ↔ IL-1b, IL-1ra, IL-10 Nemet et al 2002 [ 38 ], wrestling 11 high school boys, aged range 14–18.5 years IL-6, TNF-α, IGF-1, IGFBP1, IGFBP3, IL-1ra, IL-1b A single, typical, 1.5 h wrestling practices session.…”
Section: Resultsmentioning
confidence: 99%
“…Blood samples collected pre- and post-training In both genders, after test: ↔IL-1ra, ↑IL-6 Eliakim et al 2013 [ 29 ] volleyball 13 female, national team level players, age 16.0 ± 1.4 years GH, IGF-I, IGFB3, C, IL-6, IL-1ra Samples obtained pre-, post-, 1 h post a volley training at preseason and after 7 weeks of preparation In both conditions, athletes had: ↑IL-6, ↔IL-1ra Jurimae at al. 2018 [ 56 ], rowing 15 female rowers, age 18.3 ± 1.6 years IL-2, IL-4, IL-6, IL-8, IL-10, TNF-α, IL-1α, IL-1β, VEGF, MCP-1 Blood samples pre- and 1 h post-endurance exercise ↑IL-6, IL-8, VEGF, MCP-1 Meckel et al 2009 [ 37 ], handball 12 junior handball players, age range 17–20 years GH, IGF, IL-6, IL-1b, IL-1ra, IL-10 Sprint run on a treadmill, at an intensity of 80%. Samples collected at pre-, after each 250-m run, and 60 min post-last 250 m After exercise athletes displayed: ↑IL-6, ↔ IL-1b, IL-1ra, IL-10 Nemet et al 2002 [ 38 ], wrestling 11 high school boys, aged range 14–18.5 years IL-6, TNF-α, IGF-1, IGFBP1, IGFBP3, IL-1ra, IL-1b A single, typical, 1.5 h wrestling practices session.…”
Section: Resultsmentioning
confidence: 99%
“…Circulating cytokines and chemokines are reported to be good markers of cardiovascular demand (CD) and cardiorespiratory fitness (Jürimäe et al, 2018). However, the immune-inflammatory responses, as elicited by cytokine profiling, may differ in different physical training type.…”
Section: Introductionmentioning
confidence: 99%
“…In athletes, symptoms of respiratory disease are routinely observed as they approach competition, which can affect their exercise performance (Bermon, 2007;He et al, 2013). Jürimäe et al (2018) observed that exercise performance is associated with enhanced secretions of interleukin (IL)-2, IL-6, IL-8, vascular endothelial growth factor (VEGF), and monocyte chemoattractant protein-1 (MCP-1) (Jürimäe et al, 2018). These and many other immune-inflammatory cytokines can trigger a broad range of actions that require further elucidation in different sport training formats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the current paper does not investigate possible aetiological causes that could justify these biomechanical changes in the pulmonary circulation, in normal conditions athletes are known to have greater pulmonary and systemic vasodilation capacity 19 due to a reduction in endostatin production (antiangiogenic factor) 20 and an increase in nitric oxide production through increased function of endothelial nitric oxide synthetase. 21 However, it has also been reported that endurance exercise can increase the production of inflammatory cytokines 22 and angiotensin II, 23 which could induce vascular changes and favour poor adaptation to physical exercise.…”
mentioning
confidence: 99%